Potensi Dark Tourism Di Bandung - DIni Rahmawati (Media Wisata, 2018)
Bandung has been famous as a tourist destination or for leisure for a long time since the Dutch colonialism. Most of activities are mass tourism, such as culinary, shopping and nature tourism. Aside from those tourist activities, there is other kind of tourism that actually has been done by tourists and still need to be developed. It’s dark tourism. This research aimed to identify the potential of dark tourism and its activity. In this tourism, the object is a place with past dark horrible history for violence experienced by people in the past colonialism. The spectrum of darkest and lightest was demonstrated to show similarity and difference from previous researches as well as the level of eeriness in dark tourism.This research was conducted in Bandung using qualitative method. Data was obtained by directly visiting the tourist object, interviewed people related to the tourism activity and literature study. The instruments used in collecting data were a camera and a recorder. After processing data, it was then triangulated to make sure that all the result of the data was correct.From the research it was found that there were one tourist object and one tour included in dark tourism. They were Goa Pakar, consist of Goa Belanda and Goa Jepang, and a ghost tour which was known as Wisata Mistis. Goa Belanda and Goa Jepang are located in Taman Hutan Raya Ir. H. Djuanda or known as Goa Pakar or Dago Pakar. These caves have dark history about the cruelty from struggling against Dutch and Japanese colonialism. While ghost tour is a trip related to visiting spooky places at night. It is expected in the future that the dark tourism object will obtain serious attention and improvement from the local government so that educate tourists about sacrifice of the people who fought for nation independence